Experimental evaluation of the effectiveness of organizational and methodological principles to improve motor function in pre-school physical education - Балацька [Balatska L.] Лариса Василівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> 1024x768 <![endif]–> The efficiency of the developed organizational and technical foundations to improve motor function in preschool children during physical education in preschool education. Using conventional methods defined orientation manual motor asymmetry 165 girls and 169 boys five years involved in forming a one year experiment in the study groups, and teacher testing using motor tasks defined program for preschools – dynamic motor performance, air ’associated with manual dexterity. Advantage of girls experimental groups over the control groups of girls with different orientation manual motor asymmetry, as well as the advantage in boys by the number of indicators improved significantly during the study, and that marked the end of the highest values. The results indicate the need to use the proposed basis for the organization of physical education and of its content in pre-school. <!–[if gte mso 9]> Normal 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>